2000
DOI: 10.1037/0022-3514.79.5.776
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the interpersonal self: Strategic self-regulation for coping with rejection sensitivity.

Abstract: People high in rejection sensitivity (RS) anxiously expect rejection and are at risk for interpersonal and personal distress. Two studies examined the role of self-regulation through strategic attention deployment in moderating the link between RS and maladaptive outcomes. Self-regulation was assessed by the delay of gratification (DG) paradigm in childhood. In Study 1, preschoolers from the Stanford University community who participated in the DG paradigm were assessed 20 years later. Study 2 assessed low-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
318
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(343 citation statements)
references
References 77 publications
(185 reference statements)
19
318
1
5
Order By: Relevance
“…These youth are less likely to use drugs, be arrested for and convicted of crimes, and develop psychiatric disorders. In early adulthood, these youth also show better physical health (3)(4)(5)(6)(7)(8). These associations are generally independent of confounds like demographic characteristics, general intelligence, and psychiatric history.…”
mentioning
confidence: 82%
“…These youth are less likely to use drugs, be arrested for and convicted of crimes, and develop psychiatric disorders. In early adulthood, these youth also show better physical health (3)(4)(5)(6)(7)(8). These associations are generally independent of confounds like demographic characteristics, general intelligence, and psychiatric history.…”
mentioning
confidence: 82%
“…Indeed, it is important to note that this study links to Mischel's [37 -40] seminal research on self-control abilities, as assessed by a parallel DG task to the one used in this study. Specifically, in humans, Mischel and co-workers have found DG abilities at age 4 years to predict planning and reasoning abilities, control in the context of negative emotions, coping and even standardized testing scores at 16 -18 years of age [38,39], and higher educational attainment, better coping with stress, lower interpersonal difficulties and substance use, and even higher self-esteem and self-worth more than 20 years later [40]. Whereas a number of tasks have been used in the literature to assess self-control abilities, a number of limitations exist.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the tendency to apply self-control strategies remains remarkably consistent throughout life. For example, Mischel and colleagues found that a child's performance at age 4 on an instant gratification task (one cookie now, or two cookies later) predicted later in life their cognitive control (Eigsti et al, 2006), ability to concentrate, self-control, interpersonal competence, SAT scores, and their drug use (Mischel et al 1988;Mischel et al, 1989;Shoda et al, 1990;Ayduk et al, 2000).…”
Section: Measurement Of Conflict Identification and Of Trait Self-conmentioning
confidence: 99%